(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) in Sindulang Village, Cimanggung District, Sumedang Regency, aims to enhance agricultural productivity by utilizing renewable energy and implementing smart irrigation systems. The main problems faced by the partners are limited access to energy and a manual irrigation system that is labor- and water-intensive. This program involved 20 members of the Baruimun-Hill Farmers’ Group with activities including surveys, training on the practice of using and maintaining rooftop solar power plants (PLTS) and Smart Watering systems, the installation of an off-grid Solar Power Plant (PLTS), and the application of IoT-based Smart Watering. The implementation results demonstrated irrigation efficiency, with watering time reduced from approximately 4 hours to 1.5–2 hours per session, and irrigation points reduced from three points to two. The application of PLTS successfully eliminated electricity operational costs that were previously incurred, while supplying electrical energy for water pumps, lighting, and IoT devices. Questionnaire results indicated that understanding of the use and maintenance practices of rooftop PLTS and Smart Watering increased from 29% to 76%.